Answer:
B
Explanation:
To solve by factoring equate the expression to zero, that is
2p² - 3p - 2 = 0
Consider the factors of the product of the p² term and the constant term which sum to give the coefficient of the p- term.
product = 2 × - 2 = - 4 and sum = - 3
The factors are - 4 and + 1
Use these factors to split the p- term
2p² - 4p + 1p - 2 = 0 ( factor the first/second and third/fourth terms )
2p(p - 2) + 1(p - 2) = 0 ← factor out (p - 2) from each term
(p - 2)(2p + 1) = 0
Equate each factor to zero and solve for x
p - 2 = 0 ⇒ p = 2
2p + 1 = 0 ⇒ 2p = - 1 ⇒ p = -